2010
DOI: 10.1002/jsfa.3776
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of proteolysis profile of Argentinean sheep cheeses made by two different production methods

Abstract: S cheeses had a low proteolysis level and a soft flavour, making them appropriate for consumption after a short ripening time. L cheeses had a higher proteolysis level and more intense sensory characteristics, making them appropriate for consumption after a longer ripening time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These peaks are likely belong to some amino acids (e.g. Tyr, Phe, Trp) with eluted early retention time (Candioti et al ., ). The concentration of these peaks in OV cheese increases and more pronounced after 60 or 90 days of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are likely belong to some amino acids (e.g. Tyr, Phe, Trp) with eluted early retention time (Candioti et al ., ). The concentration of these peaks in OV cheese increases and more pronounced after 60 or 90 days of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…() and Candioti et al . () have reported higher values of WSN in ovine milk cheese (about 36.9, 10.8, 32, 11.55, 19.04 and 22%, respectively). This may be due to differences in technological parameters and other factors such as salt levels in the cheese (Mallatou et al .…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, α‐casein is mainly degraded by chymosin (Candioti et al . ). As a consequence, it can be concluded that further degradation of α‐casein may be attributed to the presence of more chymosin in commercial rennet.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations